Identity without Lack: Reflecting on Three Memory Images - Jonutytė, Jurga (Tautosakos darbai, 2017)
Employing several perspectives, the article deals with different individual attitudes towards the social and material environment. The subject of analysis comprises everyday life trajectories of three individuals that could formally be defined as “weirdos” expelled by the Soviet society, and the peculiarities of their attitude to the living environment. All these three people were rather elderly in the 1980s, and had completely established their peculiar individual relationship with their own life. The most vivid aspects of this individuality are completely at odds with standard ways of shaping the modern identity and with social roles enforced (or cultivated underhand) by the Soviet regime. The author of the article demonstrates that minimalistic living surroundings in each case can indicate entirely different context of the human life. Thus, external poverty of the individual living conditions can testify to absolutely different attitudes and discrepant experiences. The question is, to what extent does common social norms and publicly shaped patterns implying scales for measuring human worth apply to individual lives? The author goes on to give critical discussion of concepts defining the essentialist society and the related individual identity that is allegedly shaped by making constant choices and following socially valid patterns, as well as presenting the possibility of contingent identity without lack.